Requirements for a Coastal Hazards Observing System - Benveniste, Jérôme; Cazenave, Anny; Vignudelli, Stefano; Fenoglio-Marc, Luciana; Shah, Rashmi; Almar, Rafael; Andersen, Ole; Birol, Florence; Bonnefond, Pascal; Bouffard, Jérôme; Calafat, Francisco; Cardellach, Estel; et al. (Frontiers in Marine Science, 2019)
Coastal zones are highly dynamical systems triggered by a variety natural and anthropogenic forcing factors, that include sea level rise, extreme events, local oceanic and atmospheric processes, ground subsidence, etc. However so far, they remain poorly monitored on a global scale. To better understand changes affecting world coastal zones and to provide crucial information to decision-makers involved in adaptation to and mitigation of environmental risks, coastal observations of various types need to be collected and analyzed. In this white paper, we first discuss the main forcing agents acting on coastal regions (e.g., sea level, winds, waves and currents, river runoff, sediment supply and transport, vertical land motions, land use) and the induced coastal response (e.g., shoreline position, estuaries morphology, land topography at the land-sea interface and coastal bathymetry). We identify a number of space-based observational needs that have to be addressed in the near future to understand coastal zone evolution. Among these, improved monitoring of coastal sea level by satellite altimetry techniques is recognized as high priority. Classical altimeter data in the coastal zone are adversely affected by land contamination with degraded range and geophysical corrections. However, recent progress in coastal altimetry data processing and multi-sensor data synergy, offers new perspective to measure sea level change very close to the coast. This issue is discussed in much detail in this paper, including the development of a global coastal sea-level and sea state climate record with mission consistent coastal processing and products dedicated to coastal regimes. Finally, we present a new promising technology based on the use of Signals of Opportunity (SoOps), i.e., communication satellite transmissions that are reutilized as illumination sources in a bistatic radar configuration, for measuring coastal sea level. Since SoOp technology requires only receiver technology to be placed in orbit, small satellite platforms could be used, enabling a constellation to achieve high spatio-temporal resolutions of sea level in coastal zones.